The Intestinal Microbiome and the Metabolic Syndrome—How Its Manipulation May Affect Metabolic-Associated Fatty Liver Disease (MAFLD) - Stephen D. H. Malnick; Sheral Ohayon Michael (Current Issues in Molecular Biology, 2023)
Metabolic-associated fatty liver disease (MAFLD) is now the predominant liver disease worldwide consequent to the epidemic of obesity. The intestinal microbiome (IM), consisting of the bacteria, fungi, archaea, and viruses residing in the gastrointestinal tract, plays an important role in human metabolism and preserving the epithelial barrier function. Disturbances in the IM have been shown to influence the development and progression of MAFLD and play a role in the development of metabolic syndrome (MS). The main treatment for MAFLD involves lifestyle changes, which also influence the IM. Manipulation of the IM by fecal microbial transplantation (FMT) has been approved for the treatment of recurrent Closteroides difficile infection. This may be administered by endoscopic administration from the lower or upper GI tract. Other methods of administration include nasogastric tube, enema, and oral capsules of stool from healthy donors. In this narrative review, we elaborate on the role of the IM in developing MS and MAFLD and on the current experience with IM modulation by FMT on MAFLD.